Assessment of the physical and psychological aspects of the current life support system on the International Space Station for sustainable space exploration - Ichimura, Shuichi; Yamashiki, Yosuke Alexandre (Frontiers in Space Technologies, 2025)
Life support systems in space have been developed to recover a certain amount of oxygen and water. However, we still rely on resupplies for gas tanks, water bags, and food. To achieve sustainable human space exploration, we must also consider the astronauts’ wellbeing. This research analyzes and assesses the status of essential life support elements, which are air, water, and food, as well as wellbeing elements, including clothing, hygiene, and healthcare, on the International Space Station. The types and quantities of resupplies for each element were estimated by synthesizing data from multiple sources and compared against baseline values established by the National Aeronautics and Space Administration (NASA) for one crew member per day. To evaluate the qualitative and psychological dimensions of dependence on resupply missions, astronaut feedback and comments documented in reports and articles from space agencies were also analyzed as important references. The results show that resupplies involve not only gas tanks and water bags but also a significant number of spare items to maintain recovery systems. Food completely relies on resupplies, and regarding wellbeing elements, although the mass supplied from Earth seems to meet the space agency’s requirements, astronauts feel uncomfortable wearing the same clothes and using the same towels for days, especially exercise clothes, which can develop odors. It was also discovered that each resupply mission is inefficient as resupplies account for only 0.21% of the total launch mass. Relying on resupply missions has been associated with negative effects on both physical and psychological aspects, such as anxiety about the risk of running out of life support consumables, issues with stowage and odors caused by waste, and stress due to complicated cargo unloading and loading transfer operations. As humans explore the Moon and beyond, frequent resupplies will become impractical due to higher launch costs and longer delivery times, and suggestions for developing technologies to realize a sustainable human presence in space are being proposed.